Distal tibiofibular synostosis after surgically resolved ankle fractures: An epidemiological, clinical and morphological evaluation of a patient sample. Issue 11 (November 2016) - Marvan, Jiri; Dzupa, Valer; Krbec, Martin; Skala-Rosenbaum, Jiri; Bartoska, Radek; Kachlik, David; Baca, Vaclav
Abstract: Introduction: Ankle fractures comprise a highly morphologically and etiologically diverse group of injuries, which includes various degrees of impairment of bone and ligamentous structures. The complete synostosis and incomplete bony bridging of tibiofibular syndesmosis are among the local late complications after surgically treated ankle fractures. Patients and method: 269 patients were evaluated, including 203 patients with Weber type-B fractures, and 66 patients with Weber type-C fractures. All patients underwent ankle radiography at standard intervals (post-operatively, 6 and 12 weeks, 6 and 12 months). The final assessment one year after osteosynthesis was performed. The study analyzed age, sex, fracture morphology, the location and morphology of ossification, functional outcomes and subjective evaluations of patient status. Results: As risk factors there were found male sex, tibiotalar dislocation, syndesmotic screw fixation and Weber type-C fractures. The severity of subjective difficulties and objective status were not dependent on the size of distal tibiofibular synostosis. Discussion and conclusion: Despite relatively extensive imaging findings of complete synostosis or incomplete bony bridging, they only limited functional outcomes to a minimal extent.